Upaya Meningkatkan Hasil Belajar Matematika Melalui PBL Pada Peserta Didik Kelas 1 Sekolah Dasar - Ulya, Naila Darojatil; Siswanto, Joko (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This classroom action research seeks to enhance the mathematics learning outcomes of SDN Mlatiharjo 01 class I students with the use of interactive PowerPoint and image media on material recognition diagrams. The method of research used is called Classroom Action Research (PTK). Two meetings were held during each of the study's two cycles. Every cycle has four stages: preparation, execution, assessment, and review. Two cycles, totalling two meetings each, were used to conduct the research. Twenty-six IB students from the class served as the research subjects. Techniques for gathering data include testing, documentation, and observation. Student learning outcomes have significantly increased, according to the research findings. During the pre-cycle, the average class score was 60%, but the learning completion percentage was only 34.61%. Completeness rose to 46.15% in cycle I, averaging 71.53%. Cycle II's completion rate of 84.61% and class average of 83.84% demonstrated even more progress. Learning outcomes and students' critical thinking abilities in mathematics have been shown to improve with the use of the PBL model and image media, particularly regarding diagram recognition material.